Carotid intima-media thickness in spondyloarthritis patients - Skare, Thelma Larocca; Verceze, Guilherme Cortez; Oliveira, André Augusto de; Perreto, Sonia (São Paulo Medical Journal, 2013)
CONTEXT AND OBJECTIVE: Accelerated atherosclerosis has become a major problem in rheumatic inflammatory disease. The aim here was to analyze carotid intima-media thickness (IMT) in spondyloarthritis (SpA) patients and correlate this with clinical parameters and inflammatory markers. DESIGN AND SETTING: Cross-sectional analytical study at Rheumatology Outpatient Clinic, Evangelical University Hospital, Curitiba. METHODS: IMTs (measured using Doppler ultrasonography) of 36 SpA patients were compared with controls. The IMT in SpA patients was associated with inflammatory markers, like erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) and Bath Ankylosing Spondylitis Disease Activity Index (BASDAI); and with clinical parameters, like axial or peripheral involvement, dactylitis, HLA B27, uveitis occurrence, Bath Ankylosing Spondylitis Functional Index (BASFI) and lipid profile. RESULTS: The mean IMT in SpA patients was 0.72 ± 0.21 mm; in controls, 0.57 ± 0.13 mm (P = 0.0007). There were no associations with ESR, CRP, BASDAI or clinical data. In univariate analysis, greater IMT was seen in patients with longer disease duration (P = 0.014; Pearson R = 0.40; 95% confidence interval, CI = 0.06 to 0.65); higher triglycerides (P = 0.02; Spearman R = 0.37; 95% CI = 0.03 to 0.64); and older age (P = 0.0014; Pearson R 0.51; 95% CI = 0.21 to 0.72). CONCLUSION: SpA patients have a higher degree of subclinical atherosclerosis than in controls, thus supporting clinical evidence of increased cardiovascular risk in rheumatic patients.